Leveraging Artificial Intelligence (AI) to Enhance Teachers’ Spoken English at an Islamic Boarding School - Mardhiah, Ainol; Hajar, Ibnu; Purwati, Diana; Muna, Hayatul; Ariani, Riska (FKIP - Universitas Riau, 2025)
Many Indonesian pesantren (Islamic boarding schools) adopt bilingual policies requiring daily English communication, yet limited teacher proficiency often hinders their effective implementation. This study investigates the use of Artificial Intelligence (AI) SpeechAce to enhance teachers’ speaking skills for daily communication in a pesantren in Lhokseumawe, Aceh, Indonesia. Using a mixed-method explanatory sequential design, 29 teachers participated in a one-month intervention consisting of AI-based practice and training, pre- and post-tests, reflective logbook, and semi-structured interviews. Quantitative results revealed consistent improvement across pronunciation, fluency, vocabulary, and grammar, with vocabulary and grammar showing the greatest gains. Qualitative findings highlighted teachers’ positive perceptions of AI in promoting self-regulated learning and as an anxiety-reducing tool for speaking practice, despite challenges such as technical issues and the need for a longer and a more structured guidance from a human-teacher. While AI SpeechAce effectively enhanced teachers’ speaking confidence through safe, feedback-driven practice relevant to their daily communication, its limitations shaped by linguistic gaps and technical challenges, underscore the need for future blended models and extended interventions to ensure stronger transfer into real-world communicative spoken English skills.